Dampak Implementasi Mereka Belajar Kampus Merdeka Terhadap Keterampilan Mahasiswa Program Studi Pendidikan Matematika Universitas Alwashliyah - Harahap, Yenni Novita; Siswadi, Siswadi (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2023)
In the era of society 5.0, skills are the most important value for a person, because skills can help them develop themselves holistically, prepare them for the world of work, and enable them to contribute positively to society. Implementing MBKM in learning is expected to meet the needs of graduates who are ready to face the world of work. By implementing MBKM, it means giving students the freedom to design collaborative projects and choose their own learning partners, MBKM facilitates innovation and co-creation. This research is a quantitative research that collects data through questionnaires and interviews. The highest increase was in independent learning skills, namely an increase of 45.3% and the smallest increase was in critical thinking skills, namely 37.3%. But basically every skill has improved. Skill improvement has an average of 41.8%. Thus, MBKM-based learning is expected to provide greater opportunities for students to take control of their own learning, develop their interests and talents, and better prepare themselves for future challenge.